Study on fabrication and application of unsaturated polyester composite materials reinforced with Eucalyptus/Melaleuca wood shavings - Luu Ngoc Hanh Cao; Thi Bich Thuyen Nguyen; Huynh Giao Dang; Truong Ngoc Mai Ngo; Nguyen Phuong Lan Tran; Phuc Thong Lam (CTU Journal of Innovation and Sustainable Development, 2025)
A novel strategy combining Eucalyptus/Melaleuca shavings and unsaturated polyester resin was used to fabricate composite materials with outstanding aesthetics and good mechanical strength by using a hot press and manual method. The composite material produced has a flexural strength of 49.15/49.32 MPa, tensile strength of 22.38/23.83 MPa, and impact strength of 4.89/4.76 kJ.m-2 under optimal processing conditions of 120oC, 3 minutes, 150 kg.cm-2 pressure, and 40% shaving content by volume. Treating the shavings with a 2% NaOH solution improves the interface between the shavings and resin, increasing the flexural strength of the Eucalyptus/Melaleuca shavings composite material to 77.06/77.12 MPa. Some of the manufactured products, such as table and chair tops, plant pots, desk cabinets, and wall shelves, highlight the possibilities of employing scrap shavings to create new materials for use in municipal and industrial applications.